An effect of credit to entrepreneurship and micro small and medium enterprises performance in Jambi Province - Etik Umiyati; Zulfanetti Zulfanetti (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
This research aimed at analyzing 1) an effect of micro small and medium enterprises on entrepreneurship activity, 2) an effect of micro small and medium enterprises on its performance, 3) an effect of entrepreneurship on micro small and medium enterprises performance, 4) an indirect effect of micro small and medium enterprises credit to micro small and medium enterprises through Jambi Province. This research is conducted in Jambi Province by sampling approximately 276 business owners selected according to regional representatives with purposive random sampling. PLS-SEM analysis is used in this research in which the results are 1) micro small and medium enterprises credit has a positive and significant influence on entrepreneurship, 2) micro small and medium enterprises credit has a positive and significant to micro small and medium enterprises performance, 3) micro small and medium enterprises credit has significantly positive influence to micro small and medium enterprises performance, 4) the effect of entrepreneurship to micro small and medium enterprises performance are significantly positive.